Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan - Gusti Agung Ketut Arya Wibawa, I; Indrawati, Ayu Desi (E-Jurnal Manajemen; Vol 4 No 1 (2015), 2015)
Human resources is a potential asset that must be owned by the company. Human resources are supported with good performance will bring improvements for the company so that progress towards the company's goals can be achieved. The aim in this study to determine; effect of compensation and work environment on employee performance and partial simultaneously and which variables greater influence on employee performance . PT.Delina Denpasar was the location in this study with all employees , amounting to 87 people as respondents. The analytical tool used in this study is the multiple linear regression method. Based on the results obtained in this study, variable compensation and working conditions simultaneously and partially positive significant effect on employee performance and compensation variables have a greater influence on employee performance . Keyword : performance, compensation, envinronment work